The Influence Of Tourist Attraction And Accessibility On Tourists Visiting Decisions At Museum Kepresidenan Republik Indonesia Balai Kirti - Sukmawati, Ani; Yuwantiningrum, Sri Endah; Rainanto, Bambang Hengky (Jurnal Ilmiah Pariwisata Kesatuan, 2025)
When planning a tourist trip, tourists always consider the attractions offered by a destination because each place has its own uniqueness. The decision to visit a tourist destination is influenced by several factors, including tourist attraction and ease of accessibility. If a tourist destination is easily accessible, tourists will be more interested in visiting. This research was conducted to determine the influence of tourist attractions and accessibility on tourists visiting decisions at the Museum Kepresidenan Republik Indonesia Balai Kirti. The type of research used is quantitative research, with data collection techniques through questionnaires with a sample size of 100 respondents. The analytical method used is multiple linear regression analysis using the SPSS 25 software. The results of this study show that 1) Tourist Attraction has a significant effect on the Decision to Visit, 2) Accessibility has a significant effect on the Decision to Visit, 3) Tourist Attraction and Accessibility simultaneously have an effect significant impact on tourists' decision to visit the Museum Kepresidenan Republik Indonesia Balai Kirti. This study shows that the tourist attraction variable has the strongest influence on tourist visiting decisions at Museum Kepresidenan Republik Indonesia Balai Kirti. Keywords: Tourism Attraction, Accessibility, Visiting Decision